2017
DOI: 10.1590/0103-8478cr20160795
|View full text |Cite
|
Sign up to set email alerts
|

Performance of blueberry cultivars under mild winter conditions

Abstract: Evaluation of yield performance is important to find the most adapted blueberry cultivars in a particular region. This research aimed to evaluate the flowering and hasvesting periods, the production per plant, and fruit quality of eight rabbiteye blueberry cultivars (Aliceblue, Bluebelle, Bluegem, Briteblue, Climax, Delite, Powderblue, and Woodard) and two highbush blueberries (Georgiagem and O’Neal), in mild winter conditions in Pinhais-PR. Flowering and harvesting periods, production, berry weight, size, pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…High values of this ratio, respond to higher percentages of total soluble solids (TSS) and lower TA, behaviour reported in species such as Fragaria × ananassa (Santacruz-Oviedo et al 2018) and Vaccinium spp. (Medeiros et al 2017) for which TSS/TA ratio values of up to 54.83 and 20.57, respectively, were reported. The fruits of Jpd (J. tlaxcala) showed a similar behaviour with a TSS/TA ratio of up to 56.25, with averages of TSS percentages of 10.27% and TA of 0.21% (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…High values of this ratio, respond to higher percentages of total soluble solids (TSS) and lower TA, behaviour reported in species such as Fragaria × ananassa (Santacruz-Oviedo et al 2018) and Vaccinium spp. (Medeiros et al 2017) for which TSS/TA ratio values of up to 54.83 and 20.57, respectively, were reported. The fruits of Jpd (J. tlaxcala) showed a similar behaviour with a TSS/TA ratio of up to 56.25, with averages of TSS percentages of 10.27% and TA of 0.21% (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the time points when it could demonstrate a positive effect were critical, i.e., such positive performances were not observed at other time points. Another study investigating this improvement in more detail [72] showed that a BB product, equivalent to 240 g or 1 1 2 cups of fresh BBs, can have an acute effect on cognition in children and was particularly beneficial for critical periods of brain function development. Most recently, the cognitive effects of acute BB ingestion in this group of children continued to be reported with further findings on extended memory (after 75 min) and executive function task batteries (after 3 h) [73].…”
Section: Bioavailability and Different Forms Of Bb Consumption From Animal To Human Studiesmentioning
confidence: 99%
“…It has been well established that a rich diet of fruits and vegetables yields sustainable health benefits and reduces risks of lifestyle-associated health conditions. Blueberries (BBs) are one of the fastest growing fresh produce categories due to the high demand of customers [ 1 ], who have demonstrated an increased awareness of BBs’ benefits to human health. Interestingly, BBs have been labeled a “super fruit” or “superfood” for their ability to prevent or mitigate several diseases, such as cardiovascular diseases, diabetes, and cancer [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, blueberries introduced for cultivation in the Colombian Andes flourish in the unique high-altitude environments of the region. The cool climate and specific soil conditions in the Andean foothills provide an ideal setting for these berries, contributing to their exceptional quality [29,30]. The Andean cultivation of exotic blueberries represents an opportunity for local economies, providing sustainable agricultural practices and fostering economic growth within these communities [30].…”
Section: Introductionmentioning
confidence: 99%